Respuesta de diferentes sustratos en la aclimatación de vitro-plantas de banano musa spp. en la fase de invernadero - Chapín Patiño, Maryuri Yasmín (2012)
On the farm Santa Ines of the Technical University of Machala was investigated with seven substrates to achieve the acclimatization of banana plantlets obtained by cultivar vitro techniques, in which pose the following objectives - Determine the effect of different substrates in vitro plants in the greenhouse phase. - Conduct a cost analysis. The treatments studied were: T1-Arena rice husk-humus-zeolite (25-25-25-25), T2-humus-zeolite Arena (25-50-25); T3 Arena-humus-zeolite (50-25-25) T4 Cascara rice-humus T5. Sand-Rice Husk-Zeolite; T6 and T7-humus and sand. Sand - rice husk. The variables studied were: seedling height, pseudostem diameter, leaf number issued, weight of roots. The T2 substrates; humus - sand Zeolite 25-50-25 and T6; Humus 50-59% sand met the best physicochemical conditions for the establishment and development of banana plantlets in the acclimatization stage, the substrates in T2 and T6 banana seedlings, reached the highest plant height, pseudostem diameter and number of leaves plant. Too growth in height and pseudostem diameter in the acclimation phase followed a linear trend. The period of acclimatization of the plantlets of banana var Williams was six weeks, which enables the implementation of planting programs previously planned; the cost of plant propagated by meristem technique was multiplication for $ 1.40